2011
DOI: 10.1007/s00418-011-0821-3
|View full text |Cite
|
Sign up to set email alerts
|

A failure of TNFAIP3 negative regulation maintains sustained NF-κB activation in Sjögren’s syndrome

Abstract: Sjögren's syndrome (SS) is characterized by the features of systemic autoimmunity and exocrine gland dysfunction and inflammation. Deregulated cytokine production is known to contribute to the etiology of SS but the underlying molecular mechanism is still remains to be unclear. TNF-α-induced protein 3 or TNFAIP3 is involved in the negative feedback regulation of nuclear factor-κB (NF-κB) signaling in response to specific pro-inflammatory stimuli in different cell types. To define the contribution of TNFAIP3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
6
42
0
Order By: Relevance
“…Our previous study demonstrated a higher transcriptional activity of NF-kB in SS than in normal subjects, suggesting that the NF-kB signal is important for modulating immune responses in human SGEC in this autoimmune condition. 30 Here we demonstrated that in anti-Ro/ SSA Abs-treated human SGEC increased VEGF-A expression was correlated with nuclear NF-kB translocation. The use of anti-VEGF-A mAb blocked the anti-Ro/SSA Abs-induced VEGF-A molecules and thus determined a remarkable decrease of NF-kB activation, whereas treatment with exogenous VEGF-A reversed the effect of VEGF-A neutralization.…”
Section: Tace Is Involved In Vegf-a-dependent Angiogenesis Induced Bymentioning
confidence: 61%
“…Our previous study demonstrated a higher transcriptional activity of NF-kB in SS than in normal subjects, suggesting that the NF-kB signal is important for modulating immune responses in human SGEC in this autoimmune condition. 30 Here we demonstrated that in anti-Ro/ SSA Abs-treated human SGEC increased VEGF-A expression was correlated with nuclear NF-kB translocation. The use of anti-VEGF-A mAb blocked the anti-Ro/SSA Abs-induced VEGF-A molecules and thus determined a remarkable decrease of NF-kB activation, whereas treatment with exogenous VEGF-A reversed the effect of VEGF-A neutralization.…”
Section: Tace Is Involved In Vegf-a-dependent Angiogenesis Induced Bymentioning
confidence: 61%
“…NF-kB has been shown to be chronically active in many inflammatory autoimmune diseases such as inflammatory bowel disease, 34 rheumatoid arthritis 35 and systemic lupus erythematosus 36 as well as SS. 22 In fact, we previously demonstrated enhanced levels of NF-kB activation in SS as compared with normal subjects, suggesting that the NF-kB signal is important in human salivary gland cells for modulating immune responses. 22 In the present study we found that SS Abs are able to trigger the signal transduction pathways involved in NF-kB activation leading to enhanced gene expression of proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 86%
“…22 In fact, we previously demonstrated enhanced levels of NF-kB activation in SS as compared with normal subjects, suggesting that the NF-kB signal is important in human salivary gland cells for modulating immune responses. 22 In the present study we found that SS Abs are able to trigger the signal transduction pathways involved in NF-kB activation leading to enhanced gene expression of proinflammatory mediators. As the induction of proinflammatory genes by anti-Ro/SSA Abs is complex and involves increased NF-kB-DNA binding, we tested the effect of TAPI-1 on NF-kB activation and NF-kB-mediated regulation of proinflammatory cytokines production.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations